miR-10a-5p Inhibits the Differentiation of Goat Intramuscular Preadipocytes by Targeting KLF8 in Goats - Xu, Qing; Wang, Yong; Li, Xin; Du, Yu; Li, Yanyan; Zhu, Jiangjiang; Lin, Yaqiu (Frontiers in Molecular Biosciences, 2021)
Intramuscular fat contributes to the improvement of meat quality of goats. MicroRNAs (miRNAs) have been reported to regulate adipocyte differentiation and maturation. The aim of our study was to clarify whether miR-10a-5p regulates goat intramuscular preadipocyte (GIPC) differentiation and its direct downstream signaling pathway. Goat intramuscular preadipocytes were isolated from longissimus dorsi, whose miR-10a-5p level was measured at different time point of differentiation induction. Adipogenic differentiation of the GIPCs was evaluated by Oil Red O and Bodipy staining, and the expression changes of adipogenic genes like ACC, ATGL, CEBPβ, PPARγ and so on. Related mechanisms were verified by qPCR, bioinformatic analysis, dual luciferase reporter assay, overexpression and siRNA transfection. Oil Red O and Bodipy staining both with adipogenic gene detection showed that miR-10a-5p suppressed the accumulation of lipid droplets in goat intramuscular preadipocytes and inhibited its differentiation. The dual luciferase reporter assay experiment revealed miR-10a-5p regulates goat intramuscular preadipocytes differentiation by directly binding to KLF8 3’UTR to regulate its expression. Thus, the results indicated that miR-10a-5p inhibits goat intramuscular preadipocytes differentiation by targeting KLF8, and supply a new target for fat deposition and meat quality improvement.